Growth performance and nutrient utilization of African catfish (Clarias gariepinus) fingerlings fed diets with differently fermented sesame seed (Sesame indicus) (2011)
An experiment was conducted to assess the Growth Response (GR) and Nutrient Utilization (NU) of differently processed fermented sesame seed (Sesame inducum) in the diets of Clarias gariepinus fingerlings. Three categories of Sesame Seed (SS) (undehulled, dehulled and prepressed) were fermented at room temperature. Their phytic acid and tannin content were determined pre and post fermentation. Four diets were then formulated at 40%, Crude Protein level; Diet 1 (control with 0% SS inclusion); Deit 2, Undehulled Fermented SS 25% inclusion); Diet 3 Dehulled fermented SS 25% (dehulled fermented SS 25%inclusion), and diet 4 (prepressed fermented SS 25% inclusion). These diets were fed to the fish at 3% of their body weight, two times daily for 8 weeks. Each treatment had three (3) replicates, with 10 individual fish average initial weight of 1.62g. At the end of the experiment, fish carcass (whole body) were analysed for proximate composition. Result showed that fish fed Diet 1 which is the control had the best growth performance and nutrient utilization values while fish fed Diet 2 had the poorest values for these parameters. Among the differently fermented sesame seed diets, Diet 4 had the best Growth Performance (GP) and Nutrient Utilization (NU) indicies. The Specific Growth rate and the Food Conversion Ratio of Diet 1 were better and significantly (p<0.05) different from the fermented sesame seed based diets while the protein intake of all the diets were not significantly (P<0.05) different from each other. The dehulled and prepressed based diets showed appreciable increase in GP and NU values when compared to other sesame seed fermented based diets. This observation was adjudged to be due to the reduction of tannin content from 0.066% (initial) to 0.056, 0.035 and 0.024% respectively and for phytic acid from 0.248% (initial) to 0.236, 0.216 and 0.187% in undehulled, dehulled and Prepressed Sesame Seed (PSS) based diets respectively. Fermented (PSS) based diet performed significantly (P<0.05) best when compared with other fermented sesame seed based diets, due to the fact that prepressing of the seed further reduced the concentration of the antinutritional factor.